2018
DOI: 10.1007/s40471-018-0152-1
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Assumptions Underlying Instrumental Variable Analyses: a Brief Review of Falsification Strategies and Related Tools

Abstract: Purpose of ReviewInstrumental variable (IV) methods continue to be applied to questions ranging from genetic to social epidemiology. In the epidemiologic literature, discussion of whether the assumptions underlying IV analyses hold is often limited to only certain assumptions and even then, arguments are mostly made using subject matter knowledge. To complement subject matter knowledge, there exist a variety of falsification strategies and other tools for weighing the plausibility of the assumptions underlying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
136
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(139 citation statements)
references
References 52 publications
3
136
0
Order By: Relevance
“…We use police agency dummy variables as exclusion restrictions in our heckprobit models for incarceration in jail or prison, which we might expect impact conviction but not sentencing (Bushway, Johnson, & Slocum, 2007). Since exclusion restrictions must be theoretically and substantively justified (Bushway et al., 2007; Hernán & Robins, 2006, 2017; Labrecque & Swanson, 2018), we used the literature and our knowledge of Miami's criminal justice process to select appropriate exclusion restrictions. We argue that the arresting agency helps to capture differences in the quality of evidence that might be related to conviction since some research has demonstrated differences in the evidentiary collection between law enforcement agencies (Roberts, 2015), but once convicted, the arresting agency should not influence incarceration decisions.…”
Section: Methodsmentioning
confidence: 99%
“…We use police agency dummy variables as exclusion restrictions in our heckprobit models for incarceration in jail or prison, which we might expect impact conviction but not sentencing (Bushway, Johnson, & Slocum, 2007). Since exclusion restrictions must be theoretically and substantively justified (Bushway et al., 2007; Hernán & Robins, 2006, 2017; Labrecque & Swanson, 2018), we used the literature and our knowledge of Miami's criminal justice process to select appropriate exclusion restrictions. We argue that the arresting agency helps to capture differences in the quality of evidence that might be related to conviction since some research has demonstrated differences in the evidentiary collection between law enforcement agencies (Roberts, 2015), but once convicted, the arresting agency should not influence incarceration decisions.…”
Section: Methodsmentioning
confidence: 99%
“…The monotonicity assumption: Z cannot increase X for some individuals and decrease it for others (e.g., Bollen, 2012 ; Labrecque & Swanson, 2018 ; Lousdal, 2018 ).…”
Section: Recommendations For Integrating Causality In a More Productimentioning
confidence: 99%
“…IV1 is the only assumption which can be directly quantified (37); thus, we implement models (described below) to evaluate evidence for violations of these core assumptions. Specifically, pleiotropy, wherein a variant is associated with multiple phenotypes, may invalidate an IV if said pleiotropy constitutes an alternate causal pathway between the variant and the outcome (horizontal pleiotropy) (38).…”
Section: Selection Of Genetic Instrumental Variablesmentioning
confidence: 99%